Use of the high-flow helmet CPAP non-invasive ventilation device designed in Peru in patients with severe acute respiratory syndrome (COVID-19): A prospective multicenter study - Mantari, José Luis (2024)
High-flow non-invasive ventilation (NIV) devices reduce the morbidity and mortality of COVID-19. The objective was to evaluate the use of the non-invasive ventilation device with high-flow helmet CPAP designed in Peru in patients with severe acute respiratory syndrome (COVID-19) hospitalized in the emergency services of five hospitals. Prospective multicenter and cross-sectional observational study from five hospitals from July to August 2020. 19 patients were recruited and divided into two groups (G-1 n = 10; G-2 n = 9) applying clinical and gasometric parameters as indicators of disease evolution upon hospital admission and within 24 hours. A progressive increase in these parameters was observed in those patients who used the NIV CPAP helmet within the first 24 hours. In G-01, improvement was evident in 90% (n = 9/10): PaO2 (range 48–137; average: 82.49 ± 8.07; p-value = 0.008), CO2 (25.2–51.0; 36.62 ± 2.62; p-value p = 0.327), and the PaO2/FiO2 coefficient (87–318; 191.5 ± 18.68). 10% of patients did not progress optimally, being subjected to endotracheal intubation and invasive mechanical ventilation. In G-02 the values ​​were %SatO2 (range 92–98; 96 ± 0.76) and the SaO2/FiO2 coefficient (214–228; 223.2 ± 1.80), indicating significant improvement within 24 hours (p < 0.001). It is concluded that the use of the CPAP helmet non-invasive ventilation (NIV) device contributes to improving gasometric values ​​and clinical condition. Being an alternative to recover typical cases of COVID-19 in all hospitals in Peru.